Managing Sustainable Development and Poverty Alleviation in the Islamic World (American Journal of Islam and Society, 2009)
The Centre for Poverty and Development Studies (CPDS), Faculty of Economicsand Administration, University of Malaya, hosted an internationalconference, “Managing Sustainable Development and PovertyAlleviation inthe IslamicWorld,” on 14-15 October 2008 in Kuala Lumpur, Malaysia. Thisevent attracted around 100 participants and eighteen presenters.The thematic foci reflected the understanding that the Islamic worldexhibits significant and disturbing variations in its levels and magnitudes ofsocioeconomic development, poverty incidence and prevalence, income distributionpatterns, literacy, employment, and economic growth.As these areinconsistent with Islam’s principles and ethics of distributive justice andequity, unity, and social responsibility, Muslim researchers and concernedindividuals must join the quest to devise concerted and collaborative Islamicsolutions to the challenges of sustainable development, as well as of povertyalleviation and eradication, in the Islamic world.Within an Islamic framework, the presenters analyzed poverty as asocioeconomic phenomenon from multiple perspectives. One perspectivejustifies the instrumentality of empowerment in overcoming poverty inIslamic societies. As the poor are powerless, the universal principles ofequality and justice imply a more equitable power distribution in society,and collective social action implies consultation strategies to resolve socialimperfections. InMalaysia’s three poverty-focused organizations, empowermentwas analyzed using a framework of determinants, including trustingthe organizer, local working culture, participants behaving like friends, thegovernment’s role, importance of the organization, belief in and trusting theorganization, and roles at all levels. It was established that individuals, thecommunity, and the organization widely acknowledge empowerment as asignificant determinant for success ...